Potential for using crude extract of Sarocladium oryzae for suppression of rice blast - Côrtes,Marcio V. C. B. (2014)
Crude extract of an isolate of the fungus Sarocladium oryzae (CNPAF So 20G), containing the antimicrobial cerulenin, was produced and its antagonistic potential on the rice blast pathogen Magnaporthe oryzae was asessed. Cerulenin was detected in crude extract of S. oryzae through thin layer chromatography showing a Rf value of 0.63. The quantity of cerulenin in the crude extract was 237 µg.mL-1. The in vitro inhibition of germination and appressorial formation of M. oryzae was assessed on an artificial hydrophobic surface, using eight different doses of cerulenin ranging from 0.05 to 30.0 µg.mL-1. The LD50 values calculated based on the Probit-log analysis for germination and appressorial formation were 1.298 ± 0.123 µg.mL-1 and 0.0705 ± 0.0062 µg.mL-1 of cerulenin, respectively. The 30.0 µg.mL-1 of cerulenin dose inhibited 98% and 99%, germination and appressorial formation, respectively. The mode of action of cerulenin was studied by staining conidia with Calcofluor White and fluorescent microscopy showing its effect on plasma membrane. Crude extract of S. oryzae suppressed 63% of rice blast disease in greenhouse conditions. The results indicate that a product based on cerulenin and/or S. oryzae has a great potential to be used in biological control of rice blast.